Advancing approaches for patient ergonomics: understanding and leveraging the patient work network. (September 2022) - Werner, Nicole E.; Coller, Ryan J.; Hughes, M.; Lerner Papautsky, Elizabeth; Valdez, Rupa S.
For people living with chronic medical conditions, the activities of patient work are often performed by multiple actors. These actors may be formal supports (i.e., paid, professional) such as clinicians in formal clinical settings, in-home nursing and therapies, school nurses, and respite care; or informal supports (i.e., unpaid nonprofessional) such as family and friends. Although often critical to the performance of patient work, the patient work network poses many methodological challenges. The five panelists will provide prepared remarks regarding a methodological approach to studying care networks and provide a discussion of the challenges and opportunities related to using the approach. These presentations will be followed by a discussion with the panel and the audience, moderated by the chair. This discussion will be focused on eliciting further discussion on opportunities, strategies for addressing potential challenges, and additional potential approaches to studying care networks including data collection tools and analytical methods.